Dataset for SAE 2018-01-0725 "On the Aerodynamics of an Enclosed-Wheel Racing Car: an assessment and proposal of add-on devices for a fourth, high-performance configuration of the DrivAer model" - Francisco Soares, Renan; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Expansion dataset for the SAE Technical Paper 2018-01-0725, which includes:- experimental results (Figures 10 to 18) in spreadsheet format.- summary of experimental testing conditions per run.- details of statistical analysis per blocking factor (i.e. group of testing cases).- addition of corrected coefficients for wall interference (wind tunnel area blockage of 10.2%).SUMMARY:A. Front bumper splitter:Figure 10. Front bumper splitter: influence of splitter size on aerodynamic loads.B. Forebody lateral strakes:Figure 11. Forebody lateral strakes: influence of strake size on aerodynamic loads.Figure 12. Forebody lateral strakes: influence of assembly set on aerodynamic loads.C. Rear-end spoiler:Figure 13. Rear-end spoiler: influence of spoiler angle on aerodynamic loads.Figure 14. Rear-end spoiler: influence of spoiler size on aerodynamic loads.D. Underfloor diffuser:Figure 15. Underbody diffuser: influence of the diffuser angle on aerodynamic loads.Figure 16. Underbody diffuser: influence of longitudinal separators on aerodynamic loads.E. DrivAer high-performance Fastback configuration:Figure 17. High-performance Fastback DrivAer configuration: comparison of aerodynamic loads against the standard version.Figure 18. High-performance Fastback DrivAer configuration: Reynolds number sensitivity of aerodynamic loads.SUPPLEMENTARY MATERIALS:I. Publication:Soares, R., Knowles, A., Goñalons Olives, S., Garry, K. et al., "On the Aerodynamics of an Enclosed-Wheel Racing Car: An Assessment and Proposal of Add-On Devices for a Fourth, High-Performance Configuration of the DrivAer Model," SAE Technical Paper 2018-01-0725, 2018, https://doi.org/10.4271/2018-01-0725.II. CAD geometry:Soares, Renan francisco; Olives, Sergio Goñalons; Knowles, Andrew Paul; Garry, Kevin; Holt, Jenny (2018): DrivAer hp-F: the CAD geometry pack. figshare. Collection. doi:10.17862/cranfield.rd.c.3969120.
Keywords: dataset; 'wind tunnel tests'; 'aerodynamics'; 'motorsport'; 'automotive'; 'DrivAer'; 'Cranfield University'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'